Dampak Pelatihan terhadap Kompetensi Pekerja Blue Collar Perempuan: dengan Motivasi sebagai Mediasi - Pelangi Laila Santoso; Kusni Ingsih; Hertiana Ikasari; Tito Aditya Perdana (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
Job training is an important intervention to improve the competence of blue-collar women workers amid the barriers posed by patriarchal norms and domestic workloads. This study aims to test the influence of job training on worker competence by making work motivation as a mediating variable. The subject of the study was blue-collar female workers who participated in a training program organized by the Central Java Provincial Women's Empowerment Office, with a total of 165 respondents who were selected using purposive sampling techniques. The research was quantitative and analyzed the data using the Partial Least Squares (PLS) method through SmartPLS software. The findings of the study revealed that job training has a positive and significant effect on worker competence, both directly and indirectly through the mediation of work motivation. This proves that the training designed effectively increases work motivation, which in turn significantly strengthens the knowledge, skills, and work attitudes of blue-collar female workers.